The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1037/h0100925
|View full text |Cite
|
Sign up to set email alerts
|

An independent evaluation of mode deactivation therapy for juvenile offenders.

Abstract: Juveniles who commit crimes are likely to exhibit conduct problems in their youth. Persistent and long-term antisocial behavior can be seen in very young children. To treat these children, programs must be designed to meet the needs of them on an individualized basis. Residential treatment, typically, is the answer, but research has shown its ineffectiveness. Longitudinal studies and meta-analyses have shown cognitive behavioral therapy (CBT) to be effective. Mode deactivation therapy (MDT) is a form of CBT ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 46 publications
(58 reference statements)
1
16
0
1
Order By: Relevance
“…Since the meta-analysis, two independent studies were done, which confirmed the conclusions of previous studies that mdt consistently achieved better treatment outcomes than treatment as usual and delivered impressive results compared to the pre-treatment baseline of the adolescent sample (Thoder & Cautilli, 2011; Murphy & Siv, 2011). Subsequently, two other larger family-based mdt studies by the author also confirmed the same positive results (Apsche, Bass, & Backlund, 2012; Swart & Apsche, in press).…”
Section: ■ Literature Reviewsupporting
confidence: 66%
“…Since the meta-analysis, two independent studies were done, which confirmed the conclusions of previous studies that mdt consistently achieved better treatment outcomes than treatment as usual and delivered impressive results compared to the pre-treatment baseline of the adolescent sample (Thoder & Cautilli, 2011; Murphy & Siv, 2011). Subsequently, two other larger family-based mdt studies by the author also confirmed the same positive results (Apsche, Bass, & Backlund, 2012; Swart & Apsche, in press).…”
Section: ■ Literature Reviewsupporting
confidence: 66%
“…MATCH, a cognitive behavioral therapy, improves ED faster than other programs. Apsche et al ( 436 ) and Bass & Apsche ( 438 ) described an extended version of cognitive behavioral therapy (MDT) superior to conventional cognitive behavioral therapy, especially in reducing anger and aggressive behavior in adolescents and juvenile offenders ( 435 ) (see Tables 1 , 2 ). Since up to 90% of children with ED meet criteria for a categorized disorder ( 441 ), a number of treatments are available for treating the primary disorder.…”
Section: Resultsmentioning
confidence: 99%
“…Because ED is very common, especially in children and adolescents (although only in the focus in the last decade), various treatment options primarily concentrate on this dimension (426,(435)(436)(437)(438)(439)(440)(441)(442)(443)(444).…”
Section: Preventionmentioning
confidence: 99%
“…It was also reported that adolescent offenders with high levels of impulsive/antisocial behaviours were more likely to recidivate regardless of what treatment programme they went through. Thoder and Cautilli ( 2011 ) studied 39 male adolescent sexual offenders who participated in a CBT programme called mode deactivation therapy ( Table I ). Baseline scores were compared to post-treatment scores (at 1 year) on a number of parameters and indicated a significant decrease in antisocial behaviours and a recidivism rate of sexual offences of 7% after one year without any sexual offences.…”
Section: Resultsmentioning
confidence: 99%